Potensi dan Keragaman Tumbuhan Bawah Non-Kayu Di Lahan Bera Kampung Womnowi Distrik Sidey Manokwari Papua Barat - Susanto, Slamet Arif; Budirianto, Heru Joko; Maturbongs, Agatha Cecilia; Abdi Putra, Simeon (Bioma : Berkala Ilmiah Biologi, 2021)
During successionally process the non-woody plant understory cover related to dominance of tree vegetation around successional land. Fallow land are models of secondary successional are present the land of New Guinea (Papua). The study was conducted at fallow land 15 years old Womnowi, Sidey Manokwari West Papua to determine the important value index (IVI), diversity, evenness, and describe potential species composition of vegetation non-woody plant understory cover. We used continouse line sampling method when field inventory and make purposive sampling 2x2 m each a plot 20x20 m. We had found 749 individual part of 41 species, highest IVI are Sellaginella wyldenowii (25.04%), Selaginella sp (23.44%)., and Spathoglottis plicata (14.60%), diversity index Shannon-Weiner (HÊ¹) is 3.13, and evenness (E) is 0.84. We also had found orchids and some unique Arecaceae and some species can used by local wisdom like Diplazium esculentum and Pothos spp. Based the floristic composition of analysis vegetation we temporary conclude non-woody plant understory cover are shade plant.